How psychologists in men`s English football academies evaluate their working context and adopt an appropriate professional practice framework - Feddersen, N. B.; Champ, F.; Sæther, S. A.; Littlewood, M. (The Sport Psychologist, 2023)
This study examined how psychologists working in men`s English football academies evaluate their working context when choosing a professional practice framework for guiding applied psychology provisions. Sixteen psychologists—six women and 10 men—participated in two semistructured interviews. A stepwise inductive-deductive approach in the analysis was used. The authors found that 13 of the psychologists adopted humanistic psychology as their guiding framework. In exploring the reasoning, three categories were developed: (a) motives for choosing a humanistic approach, (b) challenges when applying a humanistic approach, and (c) perpetuating stigma and restrictive assumptions regarding sport psychology. The study shows that humanistic psychology might be an effective approach to countering some dehumanizing features in the current English academy context (e.g., an overreliance on metrics). However, the Premier League, the Football Association, and other governing football organizations should notice the drawbacks of how psychologists sometimes must collude with the current system to establish psychology in the academy before later expanding provisions.